2016 Giving USA data show record donations. Issue 335 (21st July 2017) - Unknown
Abstract : Donations from America's individuals, estates, foundations and corporations reached a record $390.05 billion in 2016, according to the latest Giving USA report compiled by the Giving USA Foundation. That marks the third year in a row that giving, in inflation‐adjusted dollars, has set a record.